Milton and the parables of Jesus self-representation and the Bible in John Milton's writings - Urban, David V. (University Park, Pennsylvania The Pennsylvania State University Press, 2018)
"Examines Milton's identification with characters in Jesus's parables. Connects Milton's engagement with the parables to his self-representation throughout his poetry and prose"--Provided by publisher
Introduction : Milton's hermeneutic of parables, Milton's parabolic -- The parable of the talents and the parable of the laborers. The talented Mr. Milton : a parabolic laborer and his identity ; Samson's late call : parabolic tension and resolution in Samson Agonistes ; Abdiel and the son : Milton's ideal relationship with the two parables in Paradise lost and Paradise regained -- The parable of the wise and foolish virgin. A "virgin wise and pure" : parabolic self-reference in sonnet 9 ; The wise virgin in action : the lady of a mask ; Wise virginity lost in Paradise lost ; Perfect and recovered virginity in Paradise regained and Samson Agonistes -- The parable of the householder. "Out of his treasury things new and old" : The doctrine and discipline of divorce and De doctrina Christiana ; Milton's epic narrators and the son and Mary in Paradise regained ; Internal and external scripture in Samson Agonistes
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Milton, John -- 1608-1674 -- Criticism and interpretation; Milton, John -- 1608-1674 -- Religion; Jesus Christ -- Parables -- In literature; Bible -- In literature; English literature -- Early modern, 1500-1700 -- History and criticism